Treasure Communication Center / Ariff Budiman Ishak ... [et al.] - Ishak, Ariff Budiman; Abu Bakar, Shaiful Fahmi; Zainee, Nur Ain; Abdul Halim, Nisha; Tajudin, Mohd. Fasya (Faculty of Communication and Media Studies, 2003)
Communication is an important thing fro people to connect the people around the world. One of the communication tools is hand phone that are often used as a medium for people around the world to communicate with each other. Professional workers, middle class workers, teenagers or children used it to communicate with each other. Since there is few of bumiputera's involve in the business and still far behind, we are trying to explore this new field of business and try to open wide the scope of this business in Malaysia. We decided to name our business as Treasure Communications Center, suitable with the product that we sell that is hand phone and it's equipment.